Analysis of technological potential for utilization of waste aviation lubricating materials - Boichenko, Sergii; Yakovlieva, Anna; Kale, Utku; Nagy, András (Technology audit and production reserves, 2021)
The object of research is technologies for waste aviation oils and lubricants recycling and utilization. The work is devoted to the analysis of the current state and the assessment of the technological potential in the field of processing and disposal of aviation lubricants. The current state and dynamics of the market for the production and consumption of aviation lubricants are considered. The main properties and functions of aviation oils and lubricants are analyzed, the main technical requirements for them are formulated. A complex of physical and chemical processes that occur in lubricants during their operation and long-term storage, and lead to a loss of their quality, is considered. It is shown that the main factors of quality deterioration are high-temperature destruction, oxidation, polymerization and condensation of hydrocarbons, mixing with fuel, and pollution with inorganic compounds. The main ecological as well as economic problems associated with the aссamulation of waste lubricants are considered, their negative impact on the components of the environment and human health is described. So, the main negative effects are associated with their improper storage, discharge into water bodies or soils, as well as with their burning and the formation of toxic emissions. On the basis of this, the need for the development and implementation of integrated technologies for the disposal of waste lubricating materials is shown. The main directions, methods and technologies that are used for their utilization are presented. So, depending on the composition, quality and properties of waste lubricants, technologies for restoring their quality, processing technologies using them as raw materials for the production of similar petroleum products, technologies for obtaining low-quality fuels for stationary equipment based on them can be used. It is shown that the development and application of effective technologies for the disposal of used lubricants has a number of positive effects: minimization of the negative impact on the environment, savings and expansion of oil resources for the production of commercial petroleum products, and, as a result, saving money.